2020
DOI: 10.1038/s41598-020-77035-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanical abrasion challenge on sound and demineralized dentin surfaces treated with SDF

Abstract: This study evaluated the effect of mechanical abrasion on the surface integrity, color change (ΔE) and antibacterial properties of demineralized and sound dentin surfaces treated with silver-diammine-fluoride (SDF). The dentin specimens were divided into two groups: sound and demineralized dentin, then divided into three sub-groups, control (no-treatment), SDF, and SDF + potassium-iodide (KI). Each sub-group was further divided into two groups, one exposed to mechanical brushing and the other without brushing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 39 publications
0
25
0
2
Order By: Relevance
“…These results are corroborated by others [23], who found statistically significant higher pH at the culture medium after cariogenic challenge for SDF treated tooth surfaces compared to control and NaF treated groups, suggesting that F and Ag present in SDF have a strong effect on the inhibition of acid production by Streptococcus mutans, thus inhibiting their metabolic activity. Furthermore, although no in vitro study to date has simulated the oral environment with toothbrushing for 21 days, a recent study evaluated the mechanical effect of brushing on demineralized surfaces treated with 38% SDF and found that after 7 days of brushing, the SDF-treated dentin remained with antibacterial properties [24].…”
Section: Discussionmentioning
confidence: 99%
“…These results are corroborated by others [23], who found statistically significant higher pH at the culture medium after cariogenic challenge for SDF treated tooth surfaces compared to control and NaF treated groups, suggesting that F and Ag present in SDF have a strong effect on the inhibition of acid production by Streptococcus mutans, thus inhibiting their metabolic activity. Furthermore, although no in vitro study to date has simulated the oral environment with toothbrushing for 21 days, a recent study evaluated the mechanical effect of brushing on demineralized surfaces treated with 38% SDF and found that after 7 days of brushing, the SDF-treated dentin remained with antibacterial properties [24].…”
Section: Discussionmentioning
confidence: 99%
“…The SDF penetration throughout the entire thickness of carious lesions allows the antimicrobial effect, which is mainly derived from the silver element [ 9 , 12 , 36 ], to occur thoroughly. The exposure of reversible denatured collagen results in the precipitation of silver particles within demineralized carious dentin due to the presence of functional groups with a high affinity for silver ions, such as sulfur and nitrogen groups [ 19 , 37 ]. Silver phosphate (Ag 3 PO 4 ), silver chloride (AgCl), and silver protein complexes have been identified as the reaction products of SDF with tooth tissue in previous research [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A spectrophotometer (Vita Easy shade compact, Vita, Zahnfabrik, Bad Sackingen, Germany) was used to measure the color parameters and was expressed using International Commission on Illumination System (CIE L*a*b*) where; L* coordinate representing color luminosity (white to black), a* (green to red), and b* (blue to yellow) both representing the chromaticity of the color. The color changes (ΔE*) were calculated [9], [10] as follows:…”
Section: Methodsmentioning
confidence: 99%